2020
DOI: 10.1051/mfreview/2020035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loose abrasive mixed electrolyte on the aspect ratio of blind holes drilled in soda-lime glass by ECDM process

Abstract: Electro-Chemical Discharge Machining (ECDM) process has the potential to machine various features and 3D surfaces on glass. However, machining of high aspect ratio micro holes is a challenging problem in ECDM process. In ECDM process, the machining rate mainly depends on the availability of the electrolyte at the electrode tip. Machining accuracy like taper, entry and exit diameter of the hole at high depths is rigorously affected due to lack of electrolyte at the machining zone resulting in more taperness. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…65 The metallic (Cu) and oxide (Al 2 O 3 ) nanomaterial dispersed in the electrolyte used in the ECDM increase the depth of the hole by 21.1% and 18.7%, respectively. 66 In one more study, the electrolyte was mixed with the abrasive particle to encourage ECDD of the blind hole on the soda lime glass with precision machining. The outer diameter of through a hole drilled with the conventional electrolyte, SiC mixed electrolyte and Al 2 O 3 mixed electrolyte has the value of 1237.37 µm, 712.8 µm and 821 µm, respectively.…”
Section: Electrolytementioning
confidence: 99%
“…65 The metallic (Cu) and oxide (Al 2 O 3 ) nanomaterial dispersed in the electrolyte used in the ECDM increase the depth of the hole by 21.1% and 18.7%, respectively. 66 In one more study, the electrolyte was mixed with the abrasive particle to encourage ECDD of the blind hole on the soda lime glass with precision machining. The outer diameter of through a hole drilled with the conventional electrolyte, SiC mixed electrolyte and Al 2 O 3 mixed electrolyte has the value of 1237.37 µm, 712.8 µm and 821 µm, respectively.…”
Section: Electrolytementioning
confidence: 99%
“…These include modifying the tool shape, including using flat sidewall-flat front tool [7], side-insulated tool [8], drill bit [9], helical tool with high-speed rotation [10], internally structured tube electrode [11] and spherical tip tool [12]. Other attempts include using pulsed voltage [13,14], modifying the electrolyte constituents [15,16], adding tool motion such as rotation [17] and orbital motion [18], adding tool vibration [19], vibrating electrolyte [20] and doing magnetic assisted field machining [21,22]. It was also shown that deeper holes could be established through adding pressurized electrolyte flow [23] and by applying counter-resistant feeding through reducing the magnitude of contact force between the tool and substrate as drilling progresses [24].…”
Section: Introductionmentioning
confidence: 99%